Case Study of WhatsApp Messenger Application-based Online Learning in Elementary School - Rut Elsaday; Ubaidah Ubaidah (Indonesian Journal of Learning Education and Counseling, 2022)
The pandemic situation gives no other option for all schools to switch face-to-face learning to online learning immediately. Some schools in Indonesia were looking for the most feasible alternative by considering the availability of supporting resources both owned by the school and parents of students at home. One of the most familiar alternatives is the use of messaging applications. This study aims to describe how the planning and implementation of online learning using messaging applications are implemented in an elementary school in Greater Jakarta, Indonesia. The research used the case study method. Researchers conducted a series of data collection such as interviews, observations, surveys, and document tracking. Based on the data collected, it is known that online learning based on the WhatsApp messenger application is carried out based on a learning plan prepared by the Education Office of Greater Jakarta which can be adjusted to the needs and conditions of the school. The implementation of an online learning design was carried out using the WhatsApp messenger sharing application.